Modelling of Thermal Transient Phenomena in Axial Flux Permanent Magnet Machine Based on Coupling of Two Separeted Models - Electrical and Thermal Models - Belicova, Eva (Communications - Scientific letters of the University of Zilina, 2007)
The paper deals with transient thermal modelling of air cooled axial flux permanent magnet machine. It has a rotor with permanent magnets placed on the rotor surface situated between two stators. The simulation model consists of two equivalent circuits – electrical equivalent circuit and thermal equivalent circuit to cover various machine operations. This model can be very useful mainly in mechatronic applications in order to be sure that applied machine will manage with requirements put by operation conditions and environment roughness.